46,XY disorder of sex development due to 17-beta hydroxysteroid dehydrogenase type 3 deficiency: a plea for timely genetic testing - Grimbly, Chelsey (Int J Pediatr Endocrinol, 2016)
BACKGROUND: 17β-hydroxysteroid dehydrogenase type 3 (17βHSD3) deficiency is a rare cause of disorder of sex development (DSD) due to impaired conversion of androstenedione to testosterone. Traditionally, the diagnosis was determined by βHCG-stimulated ratios of testosterone:androstenedione < 0.8. CASE PRESENTATION: An otherwise phenotypically female infant presented with bilateral inguinal masses and a 46,XY karyotype. βHCG stimulation (1500 IU IM for 2 days) suggested 17βHSD3 deficiency although androstenedione was only minimally stimulated (4.5 nmol/L to 5.4 nmol/L). Expedient genetic testing for the HSD17B3 gene provided the unequivocal diagnosis. CONCLUSION: We advocate for urgent genetic testing in rare causes of DSD as indeterminate hormone results can delay diagnosis and prolong intervention.